Investigación sobre desinformación en España. Análisis de tendencias temáticas a partir de una revisión sistematizada de la literatura - Dr. David GARCÍA-MARÍN,Dra. Guiomar SALVAT MARTINREY (Fonseca, Journal of Communication, 2023)
Disinformation is one of the great challenges that communication research has addressed in the last five years. It is therefore necessary to establish a first state of the art on the response of Spanish researchers to this problem. This paper aims to discover the most frequent objetos of study related to disinformation published in Spanish journals, in the period 2016-2021. It is also intended to elaborate a general cartography of these topics.